The (mis)allocation of corporate news - Xing Guo; Alistair Macaulay; Wenting Song (Bank of Canada, 2024)
This paper studies how the distribution of information supply by the news media affects the macroeconomy. We document three connected facts about the media's reporting of firm news. First, media coverage is highly concentrated, focusing particularly on the largest firms in the economy. Second, firms' equity financing and investment increase after media coverage. Third, these equity and investment responses are largest among small, rarely covered firms. We then develop a heterogeneous-firm model with a media sector that matches these facts. Asymmetric information between firms and investors leads to financial frictions that constrain firms' financing and investment. The media's role in alleviating information frictions is limited by their focus on large and financially unconstrained firms. Reallocating news coverage, or allowing firms to buy coverage from outlets in a competitive market, leads to substantial increases in aggregate investment and output. The aggregate effects of media coverage therefore depend crucially on how that coverage is allocated.
Keywords: D22; D61; L11; L20; 330; Firm dynamics; Financial markets